Konseling Daring Pendukung Siswa Cerdas (KDPSC): A Preliminary Evaluation of iCBT Treatments for Indonesian Freshmen with Social Anxiety - Kurnia Yohana Yulianti; Yulia Wijayanti; Neila Ramdhani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2020)
During the transition period from adolescence to adulthood, individuals with high level of social anxiety may face challenges in their academics, social life, and career. The internet-based CBT (iCBT) module "Konseling Daring Pendukung Siswa Cerdas" (KDPSC) was developed to intervene with the social anxiety experienced by Indonesian young adults. Fifteen university freshmen with moderate to high levels of social anxiety agreed to fully participate in all sessions of the program. The sessions were conducted under the guidance of registered psychologists through the chatting platform on Google Hangouts. Indonesian version of Social Anxiety Scale for Adolescents (SAS-A) were administered during the pretest and posttest. We initially conducted a qualitative assessment during the intervention and found three emergent themes at the beginning of Session Two, namely, loneliness, the feeling of having no choice, and social withdrawal. After the end of Session Two, three emergent themes were found; 1), positive thinking, 2) feeling academically motivated, and 3) intention to open up. The main finding showed that students’ level of social anxiety after intervention (M = 58.07; SE = 3.28; t(14) = 4.250; p<0.01; Cohen’s d=0.875) was significantly lower than before intervention (M = 67.20; SE = 2.048). Further implications of the study are discussed.